Screening and preliminary identification of long non-coding RNAs critical for osteogenic differentiation of human umbilical cord mesenchymal stem cells. Issue 3 (1st March 2022) - Zheng, Xiao; Gan, Shuaiqi; Su, Cheng; Zheng, Zheng; Liao, Yihan; Shao, Jingjing; Zhu, Zhimin; Chen, Wenchuan
ABSTRACT: Human umbilical cord mesenchymal stem cells (hUCMSCs) are attractive therapeutic cells for tissue engineering to treat bone defects. However, how the cells can differentiate into bone remains unclear. Long non-coding RNAs (lncRNAs) are non-coding RNAs that participate in many biological processes, including stem cell differentiation. In this study, we investigated the profiles and functions of lncRNAs in the osteogenic differentiation of hUCMSCs. We identified 343 lncRNAs differentially expressed during osteogenic differentiation, of which 115 were upregulated and 228 were downregulated. We further analyzed these lncRNAs using bioinformatic analyses, including Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. GO and KEGG pathway analysis showed that 'intracellular part' and 'Phosphatidylinositol signaling system' were the most correlated molecular function and pathway, respectively. We selected the top 10 upregulated lncRNAs to construct six competing endogenous RNA networks. We validated the impact of the lncRNA H19 on osteogenic differentiation by overexpressing it in hUCMSCs. Overall, our results pave the way to detailed studies of the molecular mechanisms of hUCMSC osteogenic differentiation, and they provide a new theoretical basis to guide the therapeutic application of hUCMSCs. Graphical abstract: uf0001